2019
DOI: 10.1016/j.nuclphysa.2019.121615
|View full text |Cite
|
Sign up to set email alerts
|

Small-x analysis on the effect of gluon recombinations inside hadrons in light of the GLR-MQ-ZRS equation

Abstract: We present a study of the contribution of antishadowing effects on the gluon distribution functions G(x, Q 2 ) in light of the Gribov-Levin-Ryskin-Mueller-Qiu, Zhu-Ruan-Shen (GLR-MQ-ZRS) nonlinear equation at small-x, where x is the momentum fraction or Bjorken variable and Q 2 is the four momentum transfer squared or photon virtuality. In this work, we have solved the GLR-MQ-ZRS nonlinear equation using Regge like behaviour of gluons in the kinematic range of 10 −2 ≤ x ≤ 10 −6 and 5 GeV 2 ≤ Q 2 ≤ 100 GeV 2 re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The main difference between GLR-MQ equation and ZRS version is the presence of an additional antishadowing term in the latter. In our previous work [18], we have obtained solutions for gluon distribution function G(x, Q 2 ) and we had shown that our predicted results of proton's F 2 derivative dF 2 / ln Q 2 were in good agreement with the HERA data. In this work, however, we have obtained the solution of F 2 (x, Q 2 ) and F L (x, Q 2 ) structure functions from the GLR-MQ-ZRS equation.…”
Section: Introductionsupporting
confidence: 68%
“…The main difference between GLR-MQ equation and ZRS version is the presence of an additional antishadowing term in the latter. In our previous work [18], we have obtained solutions for gluon distribution function G(x, Q 2 ) and we had shown that our predicted results of proton's F 2 derivative dF 2 / ln Q 2 were in good agreement with the HERA data. In this work, however, we have obtained the solution of F 2 (x, Q 2 ) and F L (x, Q 2 ) structure functions from the GLR-MQ-ZRS equation.…”
Section: Introductionsupporting
confidence: 68%
“…In these figures, the nonlinear effects are considered at the hot-spot point (R = 2 GeV −1 ). We compared our computed results of the linear and nonlinear gluon distribution with respect to the parametrization method with PDFs of groups such as NNPDF3.0 [21], CT14 [22] and GRV92 [23] (also, one can see [24][25][26][27]). Also, in figure 1, the ratio of the NNPDF3.0 and CT14 data to the linear and nonlinear gluon distribution functions is shown.…”
Section: Resultsmentioning
confidence: 99%
“…Some analytical solutions of nonlinear QCD evolution equations incorporating parton-parton recombination can be found in ref. [14][15][16][17]. The parton-parton recombination will tame down the gluon density in the high gluon density region of the scattering process.…”
Section: Introductionmentioning
confidence: 99%